(untitled) (International relations and international law Journal, 2016)
In this article, authors attempted to define the guilt and causation as the basis of civil responsibility. For a longtime scientific disputes were about the concept of guilt, guilt and illegalityratio and the some individual authors mixes signs of guilt with signs of illegality.Most experts have come to believe that guilt is a general legal category and its concept should be the uniform for allbranches of law. Fundamental disagreements on this issue has long beenexpressed in two basic concepts, which are based on theprinciple of causation and the principle of guilt.